EL MUNICIPIO DE SAN BLAS Y LAS POLÍTICAS PARA EL DESARROLLO RURAL EN NAYARIT, MÉXICO - López Regalado, Francisca (Universidad de Costa Rica, 2015)
In recent decades, international financial agencies have stressed the importance of publicpolicies as theoretical and methodological device against the governmental centralization.In the discourse of these agencies, social participation and decentralization are the mainaxes, whereas from a critical perspective, it is appreciated as a form of appropriation ofsocial demands in order to preserve and centralize power. From the latter frame work,we analyze and discuss some changes in the Mexican state as reform stoart.115 of theConstitution and the Sustainable Rural Development Law (srdl), analysis which lead usto institutional and rural actors from the municipality of San Blas, Nayarit, aspects andvoices that, in the end, enable us to reflect about limitations and municipal possibilities indefining policies for rural development.